The role of TLR-2 IN the production of TNF-a and IL-10 by macrophage infected with a recombinant BCG (rBCG) expressing the MSP-1COF Plasmodium falciparum - Rajendran, Sasirekha D/O (Universiti Sains Malaysia, 2015)
An attenuated strain of Mycobacterium bow's BCG is the only available vaccine used for tuberculosis so far. The presence of glycolipids such as lipoarabinomannan (LAM) and lipomannan (LM) in its cell wall has encouraged the use of BCG as a recombinant vaccine vector for other pathogens, including malaria parasites. The benefits of using BCG as a recombinant vaccine vector include its ability to be ingested by professional antigen presenting cells (APCs) such as macrophage to induce pro-inflammatory responses, an important innate host defense mechanism against malaria infection. The interaction between BCG and macrophage involves several toll like receptors (TLRs) such as TLR-2. Therefore, this study was conducted to determine the role of TLR-2 in the production of inflammatory cytokines such as TNF-a and IL-10 by murine macrophage cell line, .I774A.1 infected with BCG and recombinant BCG (rBCG) clones expressing the MSP-1C of Plasmodium falciparum